Pemanfaatan Bantaran Rel sebagai "Kebun Desa Mandiri di Padukuhan Banyumeneng - Praditya, Faiz Angga; Dzakiya, Nurul; Afifa, Wardania Husna; Latifah, Rifa Nur; Nurady, Dimas (DHARMA BAKTI, 2021)
There is a rail line that leaves vacant land and former fish ponds that have not been taken care of so there are puddles of water, some land is only planted with banana trees and teak trees as well as being used as a dumping ground for garbage that has the potential to cause disease in Banyumeneng Padukuhan. In fact, during the Covid-19 pandemic, environmental hygiene has a very big influence. The low level of public awareness of the vacant land that is not being managed around the railroad tracks is also due to the lack of community organization activities due to the pandemic so that it is used as an Independent Village Garden by combining aquaponics and conventional gardening systems. The method is carried out through socialization, assistance in making installations and garden maintenance which is carried out by mutual cooperation between accompanying lecturers, PHP2D students and residents. As a result, several aquaponic installations are being and have been made by processing fish ponds into Independent Village Gardens, the results of which will be managed by residents led by each head of the RT.